Annoying expressions and propagandistic actions: arguments against inclusive language within the Columns about language of the Spanish press (1980-2020) - Pano Alamán, Ana (Círculo de Lingüística Aplicada a la Comunicación, 2022)
This paper presents the results of a qualitative pragmalinguistic analysis of the main arguments used in the Spanish press against the initiatives that have emerged in recent decades to promote the inclusive use of language. The research, which is part of the DISMUPREN and the METAPRES-COLING projects, has been carried out within a corpus of columns about language, published in the press between 1980 and 2020. The aim of the study is twofold: first, covering a period of four decades, it intends to expand the research on the treatment of inclusive language in the media; second, it aims at exploring the main topics concerning the use of an inclusive language, which have been addressed in these texts, as well as identifying the argumentative strategies adopted by their authors when they reject them.